Changes of Renal AT(1)/AT(2) Receptors and Structures in Ovine Fetuses following Exposure to Long-Term Hypoxia - Mao, Caiping (S. Karger AG, 2010)
BACKGROUND/AIMS: The present study tested the hypothesis that chronic hypoxia adversely affects renal development in the ovine fetus. METHODS: Kidneys were collected from near-term fetuses of pregnant ewes maintained at sea level or high altitude (3,801 m, PaO(2): approx. 60 mm Hg) for 110 days (n = 6 for each group). RESULTS: Long-term high altitude hypoxia reduced the fetal kidney/body weight ratio. Histological analysis showed a significant enlargement in the Bowman's space and swelling of tubule epithelial cells in the kidney of the hypoxic fetus. The histological alterations were limited to the cortical, but not medullary, zone. These alterations were associated with an increase in serum creatinine and a decrease in the BUN-to-creatinine ratio in hypoxic fetuses. Angiotensin II receptors (AT(1)R and AT(2)R) were detected in the glomerular and tubular regions of the kidney. Chronic hypoxia caused a significant increase in AT(1)R and a decrease in AT(2)R protein and mRNA abundance, resulting in a large increase in the AT(1)R/AT(2)R ratio in the fetal kidney. CONCLUSION: The results demonstrate an adverse effect of chronic hypoxia on renal AT(1)R and AT(2)R expression and functions in the fetus, suggesting a possible role of fetal hypoxia in the programming of renal diseases in fetal origins.